REFLECTIONS ON INCLUSIVE PRACTICE IN THE INITIATION SPORTS FUTSAL (Fiep Bulletin - online, 2017)
This study aims to analyze inclusive practices and their educational indicators in the sport initiation to futsal. Theresearch sought to understand how the excluded children and stigmatized participate in sports activities with other students. Asteachers feel participating in an event that aims to Sports Initiation and how they perform inclusion practices in their schools. Ourhypothesis is that the inclusion of these children will be more successful if the sports activity has not only aimed competition. Inorder to achieve the objectives outlined, the adopted methodology was restricted to a qualitative study that developed from theanalysis of the reasoned theoretical framework: inclusion practices. In addition, the survey drew on interviews with four teachersfrom Porto Alegre futsal schools, in order to verify the perception of these teachers in relation to teaching the practice of inclusionadopted by them to their schools and students. After analyzing the data, we got the following results: it was observed that theteachers believe that the sports inclusion is by the appreciation of the subject regardless of their skill or technical level. It isobserved that inclusion is an old concern and that many educators today seek ways to carry out this practice.